(untitled) (Al-NASR, 2024)
The study of Sīrah (biographies) has been an essential part of Islamic scholarship, providing deep insights into the lives of key historical figures, particularly the Prophet Muhammad (PBUH), and their impact on Islamic civilization. This research focuses on the selected Sīrah writers from the Indian subcontinent, analyzing their contributions to the field of biographical literature. These scholars, through their writings, have not only preserved the essence of Islamic history but have also contributed to the intellectual and spiritual heritage of the region. The research investigates the thematic concerns, narrative techniques, and methodologies adopted by these biographers, identifying how they have shaped perceptions of Islamic history in the subcontinent. Moreover, the study delves into the modern-day relevance of these works, emphasizing how the themes explored in these biographies, such as ethics, leadership, justice, and social responsibility, remain crucial in addressing contemporary societal challenges. By examining the impact of Sīrah literature on current Muslim thought, the research highlights how these works continue to inspire and guide individuals in navigating moral and ethical dilemmas in today’s world. The critical and reflective nature of this research aims to assess the potential for the adaptation of classical Sīrah texts for modern educational purposes, social reforms, and spiritual enrichment. Ultimately, this study demonstrates the timeless value of Sīrah writings as a bridge between past wisdom and contemporary needs, offering valuable lessons for modern-day Muslim communities in the subcontinent and beyond.